2003
DOI: 10.1029/2001jb001226
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamic implications of paleomagnetic data from Tertiary sediments in Sakhalin, Russia (NW Pacific)

Abstract: N‐S trending right‐lateral strike‐slip faults, which were active in the Tertiary, transect Sakhalin, Russia, while Mesozoic forearc and accretionary rocks testify to an earlier period of subduction. Several kinematic models have been proposed for the region, but the details required to constrain these models, such as the timing of the transition from subduction to strike‐slip tectonics in Sakhalin, are still unknown. Even first‐order tectonic features, such as the boundaries of the plates with which Sakhalin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…Jackson et al (1991) proposed a method based on measurement of the anisotropy of remanence. It is effective and has been widely used (e.g., Tan and Kodama, 1998;Weaver et al, 2003;Bilardello and Kodama, 2010), but it is labour-intensive and time-consuming. Tauxe and Kent (2004) proposed an alternative method that makes use of the different properties of expected distributions for geomagnetic field directions and flattened inclinations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Jackson et al (1991) proposed a method based on measurement of the anisotropy of remanence. It is effective and has been widely used (e.g., Tan and Kodama, 1998;Weaver et al, 2003;Bilardello and Kodama, 2010), but it is labour-intensive and time-consuming. Tauxe and Kent (2004) proposed an alternative method that makes use of the different properties of expected distributions for geomagnetic field directions and flattened inclinations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The geology of Hokkaido is closely related to that of Sakhalin (Rozhdestvenskiy, 1982;Kharakhinov et al, 1985;Kimura et al, 1992a,b;Natal'in, 1993;Dobretsov et al, 1994;Fournier et al, 1994;Weaver et al, 2003). The tectonic belts on Central Hokkaido extend to Sakhalin.…”
Section: Geologic Outlinementioning
confidence: 92%
“…Fournier et al (1994) suggested that counter-clockwise rotations would be expected for Neogene basins in eastern areas of Sakhalin. Takeuchi et al (1999) and Weaver et al (2003) suggested that clockwise rotations have occurred, accommodated by 100 km scale crustal blocks, which were part of a domino system that may have extended southward to Hokkaido, based on palaeomagnetic data from Hokkaido and Sakhalin. The edges of crustal blocks should be expected to sustain tectonic deformation.…”
Section: Introductionmentioning
confidence: 97%
“…50 km within the northern part of the island since the Miocene. Based on paleomagnetic data, Weaver et al (2003) argued that fault motion in Sakhalin had begun in the Eocene and was associated with clockwise rotation. As for the southern extension, Kurita and Yokoi (2000) found a pull-apart basin in southcentral Hokkaido that formed as a result of Oligocene right-lateral slip on the Umaoi-Iburi Fault Zone (Fig.…”
Section: Contrasting Formation Mechanisms Of Older and Younger Tertiamentioning
confidence: 99%
“…1), as the northern extension of the tectonic zone, with the back-arc opening of the Japan Sea. However, their structural interpretation must be refined considering the discordant mode of block rotation detected by Weaver et al (2003). A paleoreconstruction proposed by Itoh and Tsuru (2006) suggested considerable dextral displacement on the tectonic zone but did not constrain Eocene and older relative motions because coeval sediments were lacking, because of the intense deformation of the forearc.…”
Section: Introductionmentioning
confidence: 97%